Disseminate and recurrent infundibulo-folliculitis in an Indian patient: A case report with review of literature - Sukumaran Pradeep Nair; Mini Gomathy; Gopinathan Nanda Kumar (Wolters Kluwer Medknow Publications, 2017)
A 17-year-old male patient presented with multiple discrete and confluent monomorphic skin-colored pinhead-sized follicular papules, with occasional pustules distributed on the neck, upper chest, upper posterior trunk, and proximal extremities of 4 months duration. The lesions were asymptomatic, and there was no prior history of topical application or history of atopic dermatitis. Routine investigations were normal. Histopathology of the papules showed a mononuclear infiltrate at the infundibulum of the hair follicle. We made a final diagnosis of disseminate and recurrent infundibulo-folliculitis. The patient was started on NB-UVB and topical tacrolimus. We are reporting an interesting case in an Indian patient.